Analisis Efektivitas Incentive Compatible Constraints Dalam Pembiayaan Mudharabah (Studi Pada PT. Bank Syariah Indonesia KC Medan Ahmad Yani) - Ahmad Reza Sulvira Akbar Saragih (Universitas Labuhanbatu, 2023)
This study aims to determine the background of the application to analyze the effectiveness of Incentive Compatible Constraints in mudharabah financing at Bank Syariah Indonesia KC Medan Ahmad Yani. Effectiveness comes from the word effective which means Effect, influence that can bring results. Effectiveness is a description of the level of success in achieving the goals set.. Data collection methods using interviews, observation and documentation. While the data analysis techniques used are descriptive qualitative analysis. The results showed that the implementation of incentive compatible constraints in mudharabah financing at Bank Syariah Indonesia branch office Medan Ahmad Yani was allowed because the implementation of incentive compatible constraints was proven to prevent losses incurred by customers who were not trustworthy. ICC implementation is allowed because the Bank adheres to the principle of prudence and mutual assistance in accordance with the Qur'an surah Al-Maidah Verse 2 and Al-Hujurat verse 6.